Challenges for radiative transfer 1: Towards the effective solution of conjugate heat transfer problems. (December 2018) - Howell, John R.; Mengüç, M. Pinar
Highlights: This 'challenge aper' is to establish an on-going effort for challenging conjugate heat transfer problems to be tackled by the radiative transfer community. The solutions to the four specific problems defined in the paper will be posted regularly along with detailed comparisons. In addition, new problems will be posted as needed. The first problem is to compute the radiative transfer for a series of non-premixed laminar open flames of CH4 /air for which experimental data for radiative heat fluxes are available. The second problem is to compute the radiative transfer in non-premixed turbulent flames. The third problem is for the multimode energy transfer in a catalytic reticulate porous ceramic (RPC) systems exposed to direct high-flux directional irradiation. The fourth problem is for the design and operation of the thermal processes in steel furnaces. Abstract: This paper lists crucial challenges in radiative transfer with the objective of gathering information on improving and choosing methods for solving conjugate heat transfer problems. Developments in computational and experimental techniques allow much deeper analysis of the complex problems that industry faces. Accurate and efficient solution of such multi-dimensional problems is important to reduce energy consumption in industry, with long-term positive impacts on climate change. In this paper, four challenging conjugate heat transfer problems are defined. These problems are presented with the hope of attracting researchers to solve them and provide information on the methods used and difficulties encountered. This 'challenge' is to be an on-going effort as the new solutions to these problems and the detailed comparisons are to be posted as they become available. In addition, new challenge problems will be added as needed.